2018
DOI: 10.1097/rlu.0000000000002289
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA-11 PET/CT in Newly Diagnosed Prostate Adenocarcinoma

Abstract: Introduction Prostate-specific membrane antigen (PSMA) ligand PET/CT is an emerging modality to detect the metastatic disease, especially in intermediate- and high-risk prostate cancer (PCa). In this study, we analyzed the contribution of 68Ga-PSMA-11 PET/CT in staging and therapy management of newly diagnosed PCa. Materials and Methods A total of 78 patients with biopsy-proven PCa who were referred for 68Ga-PSMA-11 PET/CT for primary staging were retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 21 publications
5
28
2
1
Order By: Relevance
“…But it is worth noting that the SUV max of primary tumor between these two subgroups has no statistical difference with a median SUV max of 8.76 (GS 7a) and 14.30(GS 7b), (P > 0.05). This nding was consistent with previous studies on 68 Ga-PSMA [23,24], which may Figure 4 showed the result of the ROC curve analysis for high-risk PCa. The AUC of the SUV max was 0.873.…”
Section: Correlation Analysissupporting
confidence: 92%
See 3 more Smart Citations
“…But it is worth noting that the SUV max of primary tumor between these two subgroups has no statistical difference with a median SUV max of 8.76 (GS 7a) and 14.30(GS 7b), (P > 0.05). This nding was consistent with previous studies on 68 Ga-PSMA [23,24], which may Figure 4 showed the result of the ROC curve analysis for high-risk PCa. The AUC of the SUV max was 0.873.…”
Section: Correlation Analysissupporting
confidence: 92%
“…Thus, we also made the pairwise comparison between different GS subgroups and found that there were statistically signi cant differences in SUV max between the subgroups of GS 6 and GS 7a, and the subgroups of GS 8-10 (P < 0.001). There was no statistical difference in SUVmax value between tumors with 7b and those with GS of 8-10, which was different from the result of previous studies on 68 Ga-PSMA [23,24]. Reasons for these discrepancies remain speculative.…”
Section: Correlation Analysiscontrasting
confidence: 82%
See 2 more Smart Citations
“…Positron emission tomography in combination with computed tomography (PET/CT) imaging with Gallium‐68‐labeled (Ga‐68) prostate‐specific membrane antigen ligands (PSMA) has entered clinical practice for staging, restaging, treatment planning, and evaluating treatment response of PCa patients since 2012 . PSMA is a cell surface protein with high expression in PCa cells .…”
Section: Introductionmentioning
confidence: 99%